Cocaine-Evoked Locomotor Activity Negatively Correlates With the Expression of Neuromedin U Receptor 2 in the Nucleus Accumbens - Kasper, James M.; Smith, Ashley E.; Hommel, Jonathan D. (Frontiers in Behavioral Neuroscience, 2018)
Cocaine use disorder (CUD) is characterized by repeated cycles of drug seeking and drug taking. Currently, there are no available pharmacotherapies to treat CUD, partially due to a lack of a mechanistic understanding of cocaine-evoked alterations in the brain that drive drug-related behaviors. Repeated cocaine use alters expression of numerous genes in addiction-associated areas of the brain and these alterations are in part driven by inter-subject genetic variability. Recent findings have shown the neuropeptide neuromedin U (NMU) and its receptor NMU receptor 2 (NMUR2) decrease drug-related behaviors, but it is unknown if substances of abuse alter NMU or NMUR2 expression. Here, rats were given twice daily saline or cocaine (15 mg/kg, IP) for five days and then seven days with no treatment. All rats were then given a single cocaine treatment and locomotor activity was measured in the acute (non-sensitized) and repeated drug exposure (sensitized) groups. Immediately following locomotor assay, tissue was taken and we demonstrate that accumbal NMUR2 mRNA expression, but not NMU mRNA expression, is negatively correlated with non-sensitized cocaine-evoked locomotor activity, but the correlation is lost following cocaine sensitization. Furthermore, in a separate cohort NMUR2 protein levels also negatively correlated with cocaine-evoked locomotor activity based on immunohistochemical stereology for NMUR2 protein expression. These findings are the first to demonstrate that repeated cocaine exposure causes dysregulated expression of NMUR2 and highlight the deleterious effects of repeated cocaine exposure on neurobiological receptor systems. Restoring the normal function of NMUR2 could be beneficial to the treatment of CUD.